Gap junction protein beta 5 interacts with Gαi3 to promote Akt activation and cervical cancer cell growth - Ping Li; Jie Chen; Juan Wang; Tianbo Liu (Cell Death and Disease)
Abstract Identifying novel therapeutic targets for cervical cancer is crucial for improving patient outcomes and reducing the global burden of this disease. Gap junction protein beta 5 (GJB5) is a member of the connexin family of proteins involved in cell-to-cell communication. This study investigated GJB5’s expression and functional significance in cervical cancer. Analysis of The Cancer Genome Atlas (TCGA) data demonstrated significantly increased GJB5 mRNA expression in cervical cancer tissues compared to normal cervical epithelium. Moreover, high GJB5 expression correlated with reduced overall survival and other adverse clinical outcomes. Single-cell RNA sequencing corroborated GJB5 overexpression within the malignant tumor cell population. The downregulation of GJB5 through shRNA or CRISPR/Cas9 gene knockout techniques significantly impaired the viability, proliferation, and migratory capacity of cervical cancer cells, while concurrently inducing apoptotic processes. Conversely, the forced overexpression of GJB5 resulted in enhanced malignant behaviors. Investigations into the underlying mechanisms revealed that GJB5 is integral to the activation of the Akt-mTOR (mammalian target of rapamycin) signaling pathway. GJB5 knockdown or knockout led to diminished phosphorylation of Akt and S6 kinase, whereas GJB5 overexpression correlated with increased Akt-mTOR signaling in primary human cervical cancer cells. Additionally, we identified a novel interaction between GJB5 and the Gαi3 (G alpha inhibitory protein 3), underscoring the crucial role of GJB5 in mediating Akt activation via Gαi3. In vivo studies utilizing xenograft models provided further evidence for the oncogenic function of GJB5. The knockdown of GJB5 resulted in a marked reduction in the growth of cervical cancer xenografts. Observations of proliferation arrest, inactivation of the Akt-mTOR pathway, and the induction of apoptosis were noted in GJB5-depleted cervical cancer xenograft tissues. Collectively, these findings underscore GJB5 as a key oncogenic driver in cervical cancer and indicate that targeting GJB5 could be a promising therapeutic approach for this disease.